2015
DOI: 10.3233/jpd-140503
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognition Impairments in Mice Overexpressing Alpha-Synuclein Under the Thy1 Promoter, a Model of Pre-manifest Parkinson’s Disease

Abstract: Background: Patients with Parkinson’s disease (PD) may exhibit deficits in “Theory of Mind”, the ability to read others’ mental states and react appropriately, a prerequisite for successful social interaction. Alpha-synuclein overexpression is widely distributed in the brain of patients with sporadic PD, suggesting that it may contribute to the non-motor deficits observed in PD patients. Mice over-expressing human wild-type alpha-synuclein under the Thy1 promoter (Thy1-aSyn mice) have synaptic deficits in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
2
15
1
Order By: Relevance
“…Recent neuropathological studies indicate that Lewy bodies accumulation in several neuronal cell types in the brain can be used as an intraneuronal landmark of PD because LB formation has been reported widely, from the medulla oblongata and olfactory bulb to neocortical areas [ 53 ]. As such, the PD model developed here is by previously reported animal models [ 2 , 48 , 54 ] because the mutant α-syn overexpression in the olfactory bulb mimicked prodromal symptoms of PD. Further evaluation of this model may contribute to the development of the precocious diagnosis of PD and may be used in the future to test the efficacy of neuroprotective agents.…”
Section: Discussionmentioning
confidence: 99%
“…Recent neuropathological studies indicate that Lewy bodies accumulation in several neuronal cell types in the brain can be used as an intraneuronal landmark of PD because LB formation has been reported widely, from the medulla oblongata and olfactory bulb to neocortical areas [ 53 ]. As such, the PD model developed here is by previously reported animal models [ 2 , 48 , 54 ] because the mutant α-syn overexpression in the olfactory bulb mimicked prodromal symptoms of PD. Further evaluation of this model may contribute to the development of the precocious diagnosis of PD and may be used in the future to test the efficacy of neuroprotective agents.…”
Section: Discussionmentioning
confidence: 99%
“…The 50% mortality rate observed in Thy1-aSyn mice fed the control or DHA-deprived diets was more important than in previous reports, where rising mortality was observed only after 14 months of age (Chesselet et al, 2012;Lam et al, 2011). It should be noted that we used Thy1-aSyn mice on a fully backcrossed C57Bl/6 background, while most publications use the hybrid C57BL/6-DBA/2 background (Chesselet et al, 2012;Lam et al, 2011;Magen et al, 2015), which may have contributed to the higher and earlier mortality rate observed here. Although we did not determine the exact causes of mortality, the protective effect of the DHA diet may relate to its multiple beneficial effects on different organs, aside from the brain, during aging (Trepanier et al, 2016).…”
Section: Discussioncontrasting
confidence: 48%
“…We used mice overexpressing human, WT α-synuclein under the murine Thy-1 promoter (Thy1-aSyn) [31], which has been characterized thoroughly in the Chesselet laboratory. This mouse model reproduces multiple features of PD including motor dysfunction, nonmotor deficits, mitochondrial dysfunction, inflammation, α-synuclein pathology, and dopamine loss [15,[32][33][34][35][36][37][38][39]. Our data show that amelioration of motor deficits following treatment with CLR01 associates with clearance of buffer-soluble α-synuclein but not insoluble α-synuclein aggregates.…”
Section: Introductionmentioning
confidence: 59%